1995
DOI: 10.1073/pnas.92.2.579
|View full text |Cite
|
Sign up to set email alerts
|

Cell cycle regulation of metallothionein in human colonic cancer cells.

Abstract: Elevated levels of metallothionein (MT) found in rapidly growing tissues such as neonatal liver and various types of human tumors have suggested a role for MT in cell proliferation. To further explore this possibility we investigated the concentration of MT in human colonic cancer The present study takes a different approach to discern the role of MT in cell proliferation. It uses a sensitive anti-MT monoclonal antibody (mAb) that recognizes an epitope of rat and human MT other than the amino terminus (20). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
61
1

Year Published

1998
1998
2010
2010

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 138 publications
(63 citation statements)
references
References 64 publications
(55 reference statements)
0
61
1
Order By: Relevance
“…Using flow cytometry, the highest concentration of MT was found in cells at the end of G1 phase and at the threshold of G1/S phases [38]. Moreover, a significant MT translocation was immunocytochemically demonstrated to take place from cytoplasm to cell nucleus during S phase of cell cycle [3,15].…”
Section: Discussionmentioning
confidence: 92%
“…Using flow cytometry, the highest concentration of MT was found in cells at the end of G1 phase and at the threshold of G1/S phases [38]. Moreover, a significant MT translocation was immunocytochemically demonstrated to take place from cytoplasm to cell nucleus during S phase of cell cycle [3,15].…”
Section: Discussionmentioning
confidence: 92%
“…Nagel and Vallee (1995) reported that the level of MT during the mitotic cell cycle of human colon cancer cells reached its maximum near the G1/S boundary of the cell cycle, around the onset of DNA synthesis, raising a physiological role for MT in cell proliferation. Similarly, MT protein expression singly or in combination with PCNA expression was significantly associated with poor prognosis in oesophageal SCC in the univariate analysis, while, in the step-wise multiple regression test, neither MT expression nor PCNA could be an independent prognostic factor in oesophageal SCC.…”
Section: Discussionmentioning
confidence: 99%
“…We wondered whether the arrest in G1 was causally related to the increase in PtdIns synthesis. To test the possibility that G1 arrest induced PtdIns synthesis, cells were treated with mevastatin, an inhibitor of HMG-CoA reductase, that has been shown to cause cell cycle arrest in G1 (18), and both DNA and phospholipid synthesis were monitored. Incorporation of radiolabeled thymidine into DNA is inhibited by 59%, yet no effect is seen on the incorporation of glycerol into either PtdCho or PtdIns (Fig.…”
Section: Effect Of G1 Arrest On Ptdins Synthesismentioning
confidence: 99%